3-Iodothyronamine Activates a Set of Membrane Proteins in Murine Hypothalamic Cell Lines - Bräunig, Julia; Mergler, Stefan; Jyrch, Sabine; Hoefig, Carolin S.; Rosowski, Mark; Mittag, Jens; Biebermann, Heike; Khajavi, Noushafarin (Frontiers in Endocrinology, 2018)
3-Iodothyronamine (3-T1AM) is an endogenous thyroid hormone metabolite. The profound pharmacological effects of 3-T1AM on energy metabolism and thermal homeostasis have raised interest to elucidate its signaling properties in tissues that pertain to metabolic regulation and thermogenesis. Previous studies identified G protein-coupled receptors (GPCRs) and transient receptor potential channels (TRPs) as targets of 3-T1AM in different cell types. These two superfamilies of membrane proteins are largely expressed in tissue which influences energy balance and metabolism. As the first indication that 3-T1AM virtually modulates the function of the neurons in hypothalamus, we observed that intraperitoneal administration of 50 mg/kg bodyweight of 3-T1AM significantly increased the c-FOS activation in the paraventricular nucleus (PVN) of C57BL/6 mice. To elucidate the underlying mechanism behind this 3-T1AM-induced signalosome, we used three different murine hypothalamic cell lines, which are all known to express PVN markers, GT1-7, mHypoE-N39 (N39) and mHypoE-N41 (N41). Various aminergic GPCRs, which are the known targets of 3-T1AM, as well as numerous members of TRP channel superfamily, are expressed in these cell lines. Effects of 3-T1AM on activation of GPCRs were tested for the two major signaling pathways, the action of Gαs/adenylyl cyclase and Gi/o. Here, we demonstrated that this thyroid hormone metabolite has no significant effect on Gi/o signaling and only a minor effect on the Gαs/adenylyl cyclase pathway, despite the expression of known GPCR targets of 3-T1AM. Next, to test for other potential mechanisms involved in 3-T1AM-induced c-FOS activation in PVN, we evaluated the effect of 3-T1AM on the intracellular Ca2+ concentration and whole-cell currents. The fluorescence-optic measurements showed a significant increase of intracellular Ca2+ concentration in the three cell lines in the presence of 10 µM 3-T1AM. Furthermore, this thyroid hormone metabolite led to an increase of whole-cell currents in N41 cells. Interestingly, the TRPM8 selective inhibitor (10 µM AMTB) reduced the 3-T1AM stimulatory effects on cytosolic Ca2+ and whole-cell currents. Our results suggest that the profound pharmacological effects of 3-T1AM on selected brain nuclei of murine hypothalamus, which are known to be involved in energy metabolism and thermoregulation, might be partially attributable to TRP channel activation in hypothalamic cells.